Facebook y TikTok como plataformas publicitarias para la fundación comunitaria Kapak Urku - Chavarrea Barrigas, Valery Michel (2024)
The Kapak Urku Community Foundation is a private non-profit organization whose mission is to contribute to social well-being and carry out projects for a sustainable economy, which is born from the needs of the community, but this has a negative effect since currently it is not is well positioned. Facebook and TikTok are platforms with different tools that offer a more efficient way to find information, contact other users, spread messages, and position a brand in a dynamic and creative way. Taking into account the aforementioned that a social network is an online community where millions of users interact with each other, the design and implementation of advertising strategies for the Kapak Urku Community Foundation would provide the possibility of designing online advertising campaigns on social networks such as Facebook and TikTok properly segmented, with the aim of positioning it.